Islamic Business Ethics: The Key to Success in Family Business (Case Study at Green Hotel Ciamis) - Kiki Hardiansyah; Fitranty Adirestuty (Review of Islamic Economics and Finance, 2021)
AbstractPurpose – This study aims to describe and analyze the application of Islamic business ethics as a necessary component of family business success. The study's subject is a family business in Ciamis Regency, West Java. Islamic business ethics indicators are based on five axioms: monotheism, balance, free will, Ihsan, and responsibility.Methodology - The research method employed is qualitative, using a phenomenology approach, case study and library research. The research data were gathered through observation, interviewing, and documenting.Findings - The research data were gathered through observation, interviewing, and documenting. According to the findings of this study, family businesses seeking success must adhere to Islamic business norms, including monotheism, balance, free choice, Ihsan, and accountability.Keywords: Islamic Business Ethics, Key to Success, Family Business